Materializations of oricha voice through divinations in Cuban Santería - Kristina Wirtz (Journal de la Société des Américanistes)
In this essay I explore how oricha (deities’) voice is produced in and through Cuban Santería practices that render oricha speech audible, meaningful, and quotable. In the semiotic order governing Cuban popular religious practice, human bodies and other objects can be “activated” as instruments of oricha speech. Divination objects such as cowry shells are understood to be the “tongue” of the oricha, through which the deities and spirits of the dead speak just as surely as when speaking through a possessed devotee or transmitting a message through a human medium. Oricha voices emerge most audibly in divinations and possession speech, although I will argue that the material processes that produce them exceed these specific ritual moments, and that orichas also can speak outside of ritual settings that elicit them. The analysis shows how approaching voice as a material phenomenon, sensible and physical, also activates its potential as a marker of social personhood, agentive force, and even biographical individuality. I trace the qualia of materials themselves and in flows of material substances and interconversions across objects, each contributing their own affordances, to argue for the central importance of transduction or signal conversion across media, and equilibration or the production of equivalences in producing oricha voice.